THE IMPLEMENTATION OF STRATEGIES FOR ENHANCING STUDENTS’ COMMUNICATIVE COMPETENCE IN MEDICAL ENGLISH COURSE - Šelmić, Nataša (Acta medicae Medianae, 2023)
In the contemporary world, English is considered to be the dominant language of communication in the field of medicine. The aim of this paper is to present specific features of the Medical English course indispensable for the successful education and professional development of medical students. It is believed that an integrative and interdisciplinary approach in which the student is at the centre of the teaching/learning process is the fundamental aspect of the Medical English course Therefore, students should be encouraged to adapt and upgrade the language skills applicable in future professional setting. The English language learning strategies at the tertiary level include acquiring medical terminology, upgrading oral and written communication, and following medical literature. Moreover, Medical English practitioners should combine different approaches based on their experience leading to the most appropriate teaching outcomes.
Keywords: Medical English, medical terminology, professional development, teaching/learning process, language skills